Overexpression of the PtSOS2 gene improves tolerance to salt stress in transgenic poplar plants. Issue 7 (30th January 2015) - Yang, Yang; Tang, Ren‐Jie; Jiang, Chun‐Mei; Li, Bei; Kang, Tao; Liu, Hua; Zhao, Nan; Ma, Xu‐Jun; Yang, Lei; Chen, Shao‐Liang; Zhang, Hong‐Xia
Summary In higher plants, the salt overly sensitive (SOS) signalling pathway plays a crucial role in maintaining ion homoeostasis and conferring salt tolerance under salinity condition. Previously, we functionally characterized the conserved SOS pathway in the woody plant Populus trichocarpa. In this study, we demonstrate that overexpression of the constitutively active form of PtSOS2 (PtSOS2TD), one of the key components of this pathway, significantly increased salt tolerance in aspen hybrid clone Shanxin Yang (Populus davidiana × Populus bolleana). Compared to the wild‐type control, transgenic plants constitutively expressing PtSOS2TD exhibited more vigorous growth and produced greater biomass in the presence of high concentrations of NaCl. The improved salt tolerance was associated with a decreased Na+ accumulation in the leaves of transgenic plants. Further analyses revealed that plasma membrane Na+/H+ exchange activity and Na+ efflux in transgenic plants were significantly higher than those in the wild‐type plants. Moreover, transgenic plants showed improved capacity in scavenging reactive oxygen species (ROS) generated by salt stress. Taken together, our results suggest that PtSOS2 could serve as an ideal target gene to genetically engineer salt‐tolerant trees.